Pengaruh Pemungutan Pajak terhadap Transaksi Cryptocurrency: Analisis Kuantitatif Berbasis Data Responden di Jakarta - Rico Alfatih Cornely; Nurhastuty Kesumo Wardhani (Journal on Education, 2025)
This study aims to analyze the impact of tax collection on Cryptocurrency transactions. The sampling method was carried out by distributing questionnaires directly to respondents using a Likert scale of 1-5, and applying the Purposive Sampling technique. The sample used in this study consisted of 100 respondents who had made Cryptocurrency transactions. Furthermore, hypothesis testing was carried out through multiple linear regression analysis using SmartPLS software version 3.2.9 and Microsoft Excel Professional 2021. The findings of this study indicate that the tax collection variable has a positive and significant effect on Cryptocurrency transactions.